Dynamics and Morphology of Meandering Rivers in Western Rajasthan, India - Singh, Surendra (Annals of Arid Zone, 2016)
Morphometric characteristics of the meandering rivers viz., amplitude. length and width of the meander belt, width of the existing channel, mean radius of curvature, their relationships and nature and size of the river. bed material are discussed in this paper. The width of the meander belt is significantly related to its length and the width of the existing channel. The length of the meander belt and amplitude are significantly related with the width of existing channel. Prediction of length, width and amplitude of the meander belt can, thus, be done by taking into account the width of the existing channel. Lands located within the meander belt from 515 10 1890 m are highly unstable and these should be avoided for constructing dams and bridges etc. In the top layers of the point and the sand bars, sediments are coarser but finer in the bottom layers.